PENINGKATAN KUALITAS DAN PEMASARAN BUDIDAYA BONSAI DI DESA ADIREJO MELALUI PENDEKATAN AGRIBISNIS - Vera Ismail; Asmarita Asmarita; Elta Nur Azizah; Nia Wahyuni; Norma Kesumawati; Septi Nawang Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
The aim of this activity is to increase the creativity of partners in processing products made from Adenium plant raw materials so that they become products that have added value and can be economically valuable. The methods used in this activity are counseling, interviews, literature study, field observation and training. Apart from increasing knowledge, responses from participants in the form of feedback and enthusiasm of participants in following and participating in activities show that the objectives of counseling and training activities have been achieved. The results obtained are an increase in knowledge in processing Adenium plants into bonsai and increased creativity of partners in making bonsai. Increasing the marketing of Adenium bonsai plant cultivation is carried out through online Digital Marketing